Similitudes y diferencias entre dos tradiciones de Ricardo Palma y dos relatos del Inca Garcilaso de la Vega - Huárag Álvarez, Eduardo (2018)
The essay establishes a comparison between the story of the Inca Garcilaso about Aguirre, and the story that Ricardo Palma calls “The ears of the mayor.” Likewise, a comparison is made between the account of the melons and the natives who believed they had been betrayed by a letter; and the story of Palma that are titled “Carta sings”. When comparing it will be possible to notice the similarities in the narrative plot and the image of the historical personages; But also the notorious differences in the treatment of the story and the discursive style. It mentions why, probably, the writer of the traditions does not mention the Inca Garcilaso being that was the predecessor of the narrative proposal.